(untitled) (International Current Pharmaceutical Journal, 2016)
Diabetes is a metabolic disorder and a progressive disease that needs proper attention as uncontrolled diabetes can lead to various acute and chronic complications such as retinopathy, nephropathy, neuropathy, gastropathy etc. Pharmacological management of diabetes is costly and has certain side effects. There is a need for the usage of natural diet in the management of diabetes, as it will be cost effective, easy to use and having no side effects. Healthy individuals must also be aware of healthy eating routines. The purpose of this review article is to highlight the importance of dietary management of diabetes. More than 81 plant species have anti-diabetic activities. In this review article, some of the most commonly used natural anti-diabetic sources are mentioned, some of which have already been used for management of diabetes since ancient times. Tariq et al., International Current Pharmaceutical Journal, October 2016, 5(11): 97-102 http://www.icpjonline.com/documents/Vol5Issue11/02.pdf